Violência entre pares, relação pais-filhos e uso de substâncias psicoativas na adolescência - Horta, Cristina Lessa (2017)
The present Doctoral Dissertation in Clinical Psychology is composed by a theoretical and two empirical articles. The theoretical study presents a systematic review of the literature on bullying and the use of psychoactive substances in adolescents. The empirical studies are derived from two cross-sectional, school-based research projects that investigated the use of psychoactive substances and associated conditions in students from Lajeado and Sapiranga, RS, Brazil. In the year 2012, 3,547 schoolchildren, aged between 12 and 17 years, answered a self-administered questionnaire inside the classroom during the school shift. All ethical care issues were considered and the project was previously approved by the Research Ethics Committee of the Unisinos University. The data analyses of these two empirical articles were authorized by the Research Ethics Committee of the Pontifical Catholic University of Rio Grande do Sul (PUCRS). Through the systematic review about bullying and the use of psychoactive substances in adolescents a controversy between the studies regarding the association between victimization and substance use was observed. Thus, the first empirical article aimed to understand the relationship between victimization by peers and use of psychoactive substances among schoolchildren, investigating gender differences. The other empirical article report the test of the main hypothesis of this dissertation, trying to verify if the perception of a negative relation with father and / or mother, as well as psychic suffering, contribute to reported situations of victimization by peers, to greater involvement in violent behaviors (fighting and carrying weapons) and the use of a greater number of psychoactive substances in the year (polyconsumption). Considering the three studies presented, it is evident that there are still gaps in the scientific literature regarding the association between bullying victimization and use of psychoactive substances. Among students from Lajeado and Sapiranga (cities), it was possible to verify that the victimization increased the probability only for the girls to make greater use in the year of illicit substances. Victimization also increased the likelihood of greater use of alcohol in the year for girls, but this effect was not maintained after the inclusion of the psychic distress variable in the analysis model. It can also be inferred that the victimization by peers does not have direct effect on the polydrug use, which is better explained by the negative relation with father and / or mother and by the presence of psychic suffering. However, victimization had a direct and indirect effect on the greater involvement of schoolchildren with violent behaviors - fights and arms possession. Thus, the complexity of the relationship between the phenomena studied is evidenced. The relationship with parents, as well as psychic suffering, seems to mediate the relation between victimization and substance use, in addition this relation influences the association between victimization by peers and involvement in violent behavior. Although the effect of peer victimization on schoolchildren is not linear, helping parents to develop good relationships with teenager and investing in young people's mental health are important tools for reducing the harm associated with victimization . In addition, since substance use and violence are considered public health problems, and considering all these results, the importance of preventing and confronting situations of victimization in pairs is evident in order to guarantee the healthy development of youth.